Development of the Nordic Bioeconomy - Lange, Lene (TemaNord, 2016)
In 2014 NCM initiated a new project: "Test centers for green energy solutions - Biorefineries and Business needs" to strengthen Nordic bioeconomy by identifying potentials, obstacles, needs and opportunities. The Nordic bioeconomy has a unique profile: Upgrade of many types of residues also to higher value products; good collaboration between private and public sector; R&D efforts in all Nordic countries. However, shortcomings were also identified: few activities across Nordic countries beyond designated Nordic programs; too few upscaling facilities; need for improved framework conditions (within regulatory and market stimulus) for biobased products. This report is part of the Nordic Prime Ministers' green growth initiative: "The Nordic Region - leading in green growth" - read more in the web magazine "Green Growth the Nordic Way" at www.nordicway.org or at www.norden.org/greengrowth